Post-breeding at-sea movements of three central-place foragers in relation to submesoscale fronts in the Southern Ocean around Bouvetøya - Lowther, Andrew D; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg J G; Kovacs, Kit M (Antarctic Science, 2014)
Publisher: Cambridge University Press
Keywords: Bouvetøya; oseanografi; pelsseler; pingviner; satellitt; telemetri

A hindcast simulation of Arctic and Antarctic sea ice variability, 1955-2001 - Fichefet, Thierry; Goosse, Hugues; Morales Maqueda, Miguel Angel (Polar Research, 2003)
A hindcast simulation of the Arctic and Antarctic sea ice variability during 1955–2001 has been performed with a global, coarse resolution ice–ocean model driven by the National Centers for Environmental Prediction / National Center for Atmospheric Research reanalysis daily surface air temperatures and winds. Both the mean state and variability of the ice packs over the satellite observing period are reasonably well reproduced by the model. Over the 47-year period, the simulated ice area (defined as the total ice-covered oceanic area) in each hemisphere experiences large decadal variability together with a decreasing trend of ~1 % per decade. In the Southern Hemisphere, this trend is mostly caused by an abrupt retreat of the ice cover during the second half of the 1970s and the beginning of the 1980s. The modelled ice volume also exhibits pronounced decadal variability, especially in the Northern Hemisphere. Besides these fluctuations, we detected a downward trend in Arctic ice volume of 1.8 % per decade and an upward trend in Antarctic ice volume of 1.5 % per decade. However, caution must be exercised when interpreting these trends because of the shortness of the simulation and the strong decadal variations. Furthermore, sensitivity experiments have revealed that the trend in Antarctic ice volume is model-dependent.
Keywords: Sørishavet; forskning; geofysikk; havis; observasjoner; polarområdene; satellitt; sjøis

Investigating Climate Change by Digital Analysis of Blue Ice Extent on Satellite Images of Antarctica - Orheim, Olav; Lucchitta, Baerbel (Annals of Glaciology, 1990)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; klimaendringer; satellitt; telemetri